1997
DOI: 10.1302/0301-620x.79b3.0790412
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Displaced Proximal Humeral Fractures in Elderly Patients

Abstract: We randomised 40 elderly patients of mean age 74 years with displaced three-or four-part fractures of the humerus to either conservative treatment or tension-band osteosynthesis.At one year and after three to five years, clinical follow-up showed no functional differences between the two groups of patients, with optimal function achieved within one year. There were major complications only in the surgically-treated group. Radiological review showed that surgery had improved the position of the fractured humera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(18 citation statements)
references
References 27 publications
(33 reference statements)
0
18
0
Order By: Relevance
“…Management of complex proximal humerus fracture is until now controversial especially in elderly [14]. However, the functional results at long-term follow-up were found to be better in reverse shoulder arthroplasty than in hemiarthroplasty group [20] Our study has several limitations.…”
Section: Discussionmentioning
confidence: 73%
“…Management of complex proximal humerus fracture is until now controversial especially in elderly [14]. However, the functional results at long-term follow-up were found to be better in reverse shoulder arthroplasty than in hemiarthroplasty group [20] Our study has several limitations.…”
Section: Discussionmentioning
confidence: 73%
“…They concluded an absence of significant difference in patient-reported clinical outcomes between the cohorts. This finding, though similar to Zyto et al (1997), resulted in fair amounts of attention, which included a headline in the BMJ that read …"Surgery is no better than a simple sling for displaced fracture of upper arm, study finds"… (Wise 2015). A response from Hertel and Domos identified several valid points, of which a pertinent point raised was the exclusion of an uncertain number of patients from the trial for "clear indication for surgery".…”
Section: Managementmentioning
confidence: 88%
“…A surgeon commonly finds himself confronted by literature, in particular with respect to the elderly patient, when deciding upon the ideal treatment option (Zyto et al 1997;Olerud et al 2011;Olerud et al 2011b;Rangan et al 2015). In essence, one is faced with the following questions: 1.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] In contradiction to the excellent outcomes reported by Neer et al [1] for both range of motion and pain relief, numerous others have reported dichotomous outcomes with very good or very poor functional outcomes. [2,4,5] Crucial for the results of HA is normal rotator cuff functioning, which depends on achieving anatomic repositioning and healing of the tuberosities. [6][7][8][9][10][11][12] Several authors showed that the application of cerclage wire is a superior way of fixating the tuberosities to the prosthetic neck.…”
Section: Introductionmentioning
confidence: 99%